2016
DOI: 10.1103/physreva.94.062510
|View full text |Cite
|
Sign up to set email alerts
|

Production of ultracold ground-state LiRb molecules by photoassociation through a resonantly coupled state

Abstract: We report on a resonantly coupled 2(1) -4 (1) photoassociation resonance in LiRb. This pair of states displays interesting decay physics that hint at interference-like effects caused by two different decay paths. We observe decay to predominantly X 1 Σ + v = 43, with significant numbers of molecules produced in X 1 Σ + v = 2 -12. This photoassociation resonance also produces ∼300 X 1 Σ + v = 0 J = 0 molecules/second. Finally, we identify a stimulated Raman adiabatic passage transfer pathway from v = 43 to v = … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 41 publications
(55 reference statements)
0
13
0
Order By: Relevance
“…The number of trapped atoms was enhanced by applying optical pumping to both elements just before magnetic trapping. We trap as many as 6×10 8 Rb atoms and 2 × 10 7 Li atoms within the magnetic trap. For several of the measurements reported here, the atom number in each element was adjusted by reducing the MOT loading times appropriately, or by changing the composition of the effusive atomic beam by adjusting temperatures in the two-element oven.…”
Section: Preparation Of Lithium-rubidium Laser-cooled Gas Mixturesmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of trapped atoms was enhanced by applying optical pumping to both elements just before magnetic trapping. We trap as many as 6×10 8 Rb atoms and 2 × 10 7 Li atoms within the magnetic trap. For several of the measurements reported here, the atom number in each element was adjusted by reducing the MOT loading times appropriately, or by changing the composition of the effusive atomic beam by adjusting temperatures in the two-element oven.…”
Section: Preparation Of Lithium-rubidium Laser-cooled Gas Mixturesmentioning
confidence: 99%
“…Low energy collisions between these elements have previously been characterized by observing thermalization between Li and Rb gases with both atoms held in the magnetically trapped |F = 2, m F = 2 hyperfine ground state [3], via which the magnitude of the triplet scattering length for 7 Li-87 Rb collisions could be inferred. Previous measurements of collisional Fano-Feshbach resonances between atoms both in the |F = 1, m F = +1 hyperfine state, observed at large magnetic fields [4,5], together with photoassociation [6][7][8] and Raman spectroscopy [9] of several isotopologues of the LiRb molecule have led to the development of an empirically based model of the LiRb molecular potentials [5], from which the low-energy scattering amplitudes can in principle be predicted for all hyperfine-state combinations undergoing low-temperature collisions.…”
mentioning
confidence: 99%
“…Due to singlet-triplet interaction, they are often used as intermediate states in transforming the cold and ultracold molecules to their low-lying ground state, preferably to the "absolute" rovibronic ground state X 1 Σ + (v X = 0, J X = 0), suggesting a variety of applications, see [1,2] for a review. Transfer of ultracold species to the deeply bonded ground state levels via first excited electronic states was realized for RbCs [4,5], LiCs [6], NaCs [7], and LiRb [8]. Besides, the mutually perturbed states allow to access the higherlying triplet states manifold by applying multi-step laser excitation technique, which is especially favorable for heteronuclear diatomics due to absence of the u/g selection rule.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several years, a series of studies showed that short-range PA is generally possible for bi-alkali molecules: short-range PA has been demonstrated for NaCs [9], Rb 2 [10,11], LiCs [12], RbCs [13][14][15], and LiRb [16,17]. Furthermore, production of rovibronic groundstate has been verified for LiCs [12], RbCs [14,15], and LiRb [17].…”
Section: Introductionmentioning
confidence: 99%